Mass Transfer and Drop Size Distributions in Reactive Nanoparticle‐Stabilized Multiphase Systems1. Issue 11 (10th October 2017) - Petzold, Marc; Röhl, Susanne; Hohl, Lena; Stehl, Dmitrij; Lehmann, Maren; von Klitzing, Regine; Kraume, Matthias
Abstract: Mass transfer in stirred liquid‐liquid systems with and without silica nanoparticles is investigated for the saponification of benzoyl chloride. The mass transfer area is positively affected by the nanoparticles which lead to an increase of the liquid‐liquid interfacial area due to droplet coalescence hindrance. However, an additional mass transfer resistance induced by particles at the liquid‐liquid interface was observed for all particle concentrations, since the high occupancy diminishes the available area for mass transfer. The ratio of the two oppositional effects needs to be determined to identify suitable nanoparticle reaction systems. Abstract : The mass transfer in a stirred liquid‐liquid system with added nanoparticles was investigated. To determine the influence on the available mass transfer area, besides a dynamic drop size analysis a characterization of the interfacial coverage by nanoparticles was conducted. The results showed enhanced mass transfer for small particle concentrations.